An Indonesian-version of the short attitude toward mathematics inventory: a voice from pre-service chemistry teacher - Andrian Saputra; Lisa Tania (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to examine the validity of the Indonesian version of the short attitude toward mathematics inventory (ATMI). The adapted inventory was also used for further analysis to explore mathematics attitude of pre-service chemistry teachers across gender. The original ATMI was translated into Bahasa and distributed to 328 participants via the online survey. After preliminary checking for multivariate outliers, all the data were used to analyze the construct validity of structural model using confirmatory factor analysis (CFA). Furthermore, multigroup analysis with structured mean modelling was conducted to explore the gender effect toward mathematics attitude. All item means, standard deviations and correlation matrix were also explored. The result found that the short form supported the four-factor solution as the original ATMI. Modification indices, standardized regression weight, and squared multiple correlations were used to determine which items to be removed or retained during analysis until standard criteria for model fit reached. This items deletion produced a shorter version of ATMI (19 items) with fairly good internal consistency, both for all items inventory (α=0.92) or for individual subscale (mean α=0.86). Moreover, the t-test on the latent mean value showed no significant difference of attitude toward mathematics between male and female.